PENGARUH SUMBER PUPUK ORGANIK TERHADAP PENAMPILAN TEBU (Saccharum officinarum L.) PADA TATA TANAMBARIS GANDA BENIH GANDA [Effect of Organic Fertilizer Resources on Sugarcane (Saccharum officinarum L.) Performances in Double Rows Double Seeds Planting Arrangement] - Busro, Djumali; Mulyaningsih, Sri; Basuki, Teger (BERITA BIOLOGI, 2018)
Increased productivity of sugarcane in upland area can be done through the implementation of the integration of manure with a high dose of inorganic fertilizer in the double rows and twice plant populations of single row (âdouble rows double seedsâ) planting arrangement. Limited availability of manure and inorganic fertilizer entails the replacement of manure with green manure fertilizer. The research wasÂ aimed to obtain a green manure as replacement manure that can be intercropped in the double rows double seeds planting arrangement. The experiment was done in the Asembagus Experimental Station, Situbondo, East Java on January to December 2014 for plant cane (PC) and from January to December 2015 for ratoon cane (RC). Treatments were arranged in a Randomized Block Design time for replication. The treatment includes (1) the four rows of Crotalaria juncea, (2) two rows of Crotalaria juncea, (3) four rows of peanuts in width between rows of sugar cane, (4) manure, and (5) no organic fertilizer. The results showed that the integration of organic fertilizer with a low dose of inorganic fertilizers increases productivity and sugar yield 5.20 to 41.78% and 33.33 to 69.90%, respectively in PC and 7.33 to 32.67% and 5.74 to 29.61%, respectively in RC from no organic fertilizer. Four rows of Crotalaria juncea could replace the role of manure in improving the productivity and sugar yield for PC and two rows of Crotalaria juncea for RC.